(untitled) (Research, Society and Development, 2020)
The population’s growing search for healthy foods has increased significantly, causing the food industry to develop new products for the purpose of healthiness provided by functional properties. In this market, yogurts have stood out, allowing the industry to use this device as a vehicle for the inclusion of prebiotic compounds. With this, the present research had as objective to elaborate and to characterize the physicochemical properties Greek type yogurts with addition of different concentrations of the star fruit jam. Three yogurt formulations were developed with the addition of different concentrations of star fruit jam F1 (10%), F2 (15%) and F3 (20%) and were subjected to physicochemical analysis pH, total acidity, moisture, ash, proteins, lipids and total carbohydrates. For pH, the samples differed from each other under the operational conditions studied, where there was a gradual reduction in pH as the concentration of the jam in the yoghurts increased. Regarding total acidity, sample F3 (20%) presented the highest average value of total acidity, when compared with the other samples. The results obtained for the content of ash, protein and carbohydrates and moisture, the formulations developed did not show significant difference in the final concentration of these constituents. The formulations elaborated in this research presented excellent results, however, the application F1 (10%), obtained the best results when compared with the rest.